Why Has Judicial Review Failed in Japan? - David S. Law (Washington University Law Review, 2011)
The Article examines the political and institutional explanations for the failure of judicial review in Japan. It outlines the law reforms on the judicial process which affects the Supreme Court of Japan (SCJ). It concludes that the decision of the SCJ to discharge its responsibility for performing judicial review will be unlikely.
Keywords: Judicial review -- Japan; Political culture -- Japan; Japan. Daishin' in